The co-infection of Buruli ulcer and cutaneous leishmaniasis in Sudanese patient: An association by choice or by chance? - Abdelsalam M.A. Nail; Rayan Ali Tonga; Huda M. Salih; Nadir Abuzeid; Mohamed H. Ahmed (Elsevier, 2020)
Buruli ulcer and cutaneous leishmaniasis both have the similar cutaneous clinical presentation. Therefore, relying on clinical diagnosis can be challenging. We present a case of 45 years old woman diagnosed with cutaneous leishmaniasis, confirmed by skin biopsy. She received different modalities of anti-leishmanial treatment (fluconazole 450 mg daily for 4 weeks, sodium stibogluconate (SSG) followed by thermal therapy, SSG/IV 20 mg/kg for 30 days combined with paromomycin 15 mg/kg IM for 17 days). These treatments were associated with partial improvement of the ulcer and failure of healing. A second biopsy demonstrated the presence of Mycobacterium ulcerans and hence the diagnosis of Buruli ulcer as a cause of the delayed healing of the ulcer. M. ulcerans releases a toxin known as mycolactone, which decreases immune system function and results in tissue death. M. ulcerans, is regarded as the third most prevalent Mycobacterium after M. tuberculosis and M. leprae. Treatment with streptomycin intramuscular injections 1 g daily and rifampicin 600 mg daily for 8 weeks was associated with complete healing of the ulcer. To our knowledge, this is the first report that describes the co-infection of Buruli ulcer and cutaneous leishmaniasis in Sudan.